Retaining Structures in Slope Stabilization: A Comparative Analysis on Safety and Cost Effectiveness (Journal of Civil Engineering Researchers, 2025)
This study evaluates slope stabilization methods using gravity stone walls, reinforced concrete cantilever walls, and pile shoring systems. Stability and economic performance of these systems were compared through analyses conducted with Plaxis 2D and İstCAD software on a model slope subjected to increasing excavation depths. Results show that gravity stone walls are more economical up to 5 m, while cantilever walls are preferable between 5–9 m. Beyond 9 m, both methods become inadequate, and pile shoring systems provide the most effective solution. Each method's advantages and limitations were assessed based on field applicability, cost, and stability.
Keywords: Slope Stabilization; Retaining Structures; Cost-Effectiveness Analysis; PLAXIS 2D; Natural Disaster